The influence of empowering leadership on innovative behavior: through motivation, self-efficacy, and work engagement - Muhamad Arief Erdavit; Usep Suhud; Ari Saptono (International Journal of Applied Finance and Business Studies, 2023)
This research aims to examine the influence of empowering leadership, motivation, self-efficacy, and work engagement on innovative behavior in the Ministry of Youth and Sports of the Republic of Indonesia. This is a quantitative study employing an analysis method called SEM Analysis. The sample for this study consisted of 290 personnel from the Republic of Indonesia's Ministry of Youth and Sports. Only empowering leadership and self-efficacy have a substantial influence on innovative behavior, according to the findings of this study. Meanwhile, this study shows that motivation and work engagement have no effect on innovative behavior. Motivating, self-efficacy, and work engagement can all be influenced by empowered leadership